2016
DOI: 10.1016/j.ijscr.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Extremely early stage osteonecrosis of the femoral head in a patient with hip pain secondary systemic steroid pulse therapy for Vogt-Koyanagi-Harada syndrome: A case report

Abstract: HighlightsThis was a case of hip osteonecrosis with onset during intravenous corticosteroid therapy for Vogt-Koyanagi-Harada syndrome.After seven weeks, the patient was diagnosed at extremely early stage of osteonecrosis of the femoral head.She was treated with joint-preserving regenerative therapy using growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…But the amount of these cells were less than fat cells and MRI may not reflect the lesion of femoral head. MRI scan only gave the osteonecrosis signal after fat cell death (12–48 hours), when some pathologic changes appeared, such as disorder of bone trabecula, pimelosis of marrow cavity, fatty degeneration and necrosis of osteocyte and so on [ 9 ]. Through MRI and observation on histopathology, we found that joint space of femoral heads got wide slightly and had a little patchy hyperintensity round 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the amount of these cells were less than fat cells and MRI may not reflect the lesion of femoral head. MRI scan only gave the osteonecrosis signal after fat cell death (12–48 hours), when some pathologic changes appeared, such as disorder of bone trabecula, pimelosis of marrow cavity, fatty degeneration and necrosis of osteocyte and so on [ 9 ]. Through MRI and observation on histopathology, we found that joint space of femoral heads got wide slightly and had a little patchy hyperintensity round 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…At present, early diagnosis of SANFH depended on magnetic resonance imaging (MRI) scan [ 6 ]. However, the MRI only diagnose osteonecrosis after fat cell death 12–48 hours, when some pathologic changes were already generated, such as structural disorder of bone trabecula, pimelosis of marrow cavity, fatty degeneration and necrosis of osteocyte and so on [ 7 9 ]. Hence, it was meaningful to screen out risk factors of femoral head necrosis, monitor and intervene as early as possible, and prevent the emergence of early pathologic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ONFH following VKH syndrome could be diagnosed early and successfully treated by joint-preserving regenerative therapy. 25 …”
Section: Discussionmentioning
confidence: 99%
“…MRI is considered the most accurate test and is both highly sensitive and highly specific for early ONFH without symptoms. 5 7 , 10 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of osteoarthritis has risen and an increasing number of individuals have been clinically diagnosed with the condition, which presents a serious threat to human health and quality of life ( 4 , 5 ). Osteonecrosis of the femoral head is a specific type of osteoarthritis that significantly affects the patient's ability to move and exhibits the most serious degeneration of the joints among osteonecrosis diseases ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%